An Investigation Of Elements Affecting Banks Profitability And Liquidity In Financial Statement (Journal of Namibian Studies : History Politics Culture, 2023)
The economic environment in India pertaining to the banking sector has been constantly changing since 1991 policy of liberalisation privatisation and globalisation. Banking sector was dominated by the public sector banks (by about 70 to 80%) in terms of number of banks or branches government introduce series of changes in the banking sector such as deregulation of rate of interest , reduction in SLR and CRR, entry of private sector, automatic expansion of bank branches and so on.              These changes have created stiff competition in the banking sector between public sector bank and private sector banks. One of the major problems faced by public sector banks is the big jump in the NPA which rose to a figure of more than Rs.10lakh crore during the year 2020.  All these factor will have greater impact on the liquidity and profitability of the banks. Hence taking in to consideration the major changes taking place in the macroeconomic environment in the country, the present research is undertaken with respect to the major banks of the country one in public sector and another is private sector. State Bank of India was chosen from the public sector and ICICI bank was taken from private sector. The major objectives of this research was to compare the two giant banks in terms of liquidity, profitability and management financial decisions.